Spatial reticulate polytriphenylamine cathode material with enhanced capacity for rechargeable aluminum ion batteries - Tao, Fei; Wei, Guokang; Xu, Xinqi; Xu, Weize; Xie, Wei; Yang, Jianhong; Luo, Zhenhua; Li, Xin; Qiao, Jia (Springer, 2023)
Rechargeable aluminum ion batteries (RAIBs) are a very attractive option for large-scale energy storage thanks to their promising theoretical capacity, high energy density, low cost, abundant earth resources, and environmental friendliness. While the cathode materials chosen and prepared are so essential for the electrochemical performance of RAIBs that extensive efforts and research have been done. In this study, the electrochemical performances of RAIBs were optimally improved by the chemical polymerization of triphenylamine to obtain polytriphenylamine (PTPAn) as the cathode material. The polymerization process improved the spatial reticulate structure of triphenylamine, gained a three-dimensional mesh-like nanostructure, which provided more chemical reaction sites and ion reaction channels, greatly increased the specific surface area, and accelerated the electrochemical reaction kinetics. On this basis, a stable discharge-specific capacity of around 137.4 mAh g−1 was achieved at high current densities of 1 A g−1 for the PTPAn cathode, and the Coulombic efficiency was maintained at about 99% after the life of 500 cycles. The understanding and appreciation of the charging and discharging working principle of PTPAn material as RAIBs cathode, meantime, were deepened by a multitude of ex-situ experiments. These findings are anticipated to serve as the cornerstone for the subsequent development of large-scale RAIBs systems for energy storage that use organic polymers as the cathode material.
Keywords: Rechargeable aluminum ion batteries; Organic cathode; Triphenylamine; Polytriphenylamine